A carbon flow tracing and carbon accounting method for exploring CO2 emissions of the iron and steel industry: An integrated material–energy–carbon hub. (1st March 2022) - Zhang, Hanxin; Sun, Wenqiang; Li, Weidong; Ma, Guangyu
Graphical abstract: Highlights: The conventional energy hub is extended to a material flow-based energy hub. An integrated material-energy-carbon hub is proposed. Interconnection among carbon, material and energy flows of steelworks is explored. Impacts of material and energy flows on variation in CO2 emissions are discussed. Abstract: In the context of carbon neutrality, accurate carbon accounting is urgently needed for energy-intensive industries, such as the iron and steel industry. However, methods based on black-box models are rather rough and the impact of changes in a certain material and energy flow on the carbon flows of the complex production process is unclear, making it impossible to find carbon emission reduction potential in iron and steel production sites. To tackle this problem, the concept of a 'hub' is innovatively used for carbon flow tracing and carbon accounting. The conventional energy hub is extended to a material flow-based energy hub in this work, and an integrated material-energy-carbon hub is proposed. Based on the integrated carbon hub, the interconnection among carbon, material and energy flows and the impacts of various material and energy flows on the variation in CO2 emissions of iron and steel production processes are explored in a case study. Results show that the ironmaking plant contributes the most to the CO2 emissions of the whole site, and the impacts of material and energy flows on the whole-site carbon flow are significant. The effects of the scrap ratio, pig iron, ore mix, ore grade, imported coke, and pulverized coal injection are investigated. The results indicated that the proposed carbon hub is an effective tool for accurate carbon accounting and carbon flow tracing and contributes to the deep low-carbon transition pathways for the iron and steel industry.